2009
DOI: 10.1038/cr.2009.27
|View full text |Cite
|
Sign up to set email alerts
|

The differential protein and lipid compositions of noncaveolar lipid microdomains and caveolae

Abstract: Morphologically, caveolae and lipid rafts are two different membrane structures. They are often reported to share similar lipid and protein compositions, and are considered to be two subtypes of membrane lipid microdomains. By modifying sucrose density gradient flotation centrifugation, which is used to isolate lipid microdomains, we were able to separate caveolae and noncaveolar lipid microdomains into two distinct fractions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 49 publications
0
47
0
Order By: Relevance
“…For fractionation of PM microdomains, MBECs from three confluent 160-mm-diameter dishes were harvested and PM isolated and subjected to detergent-free sodium carbonate extraction and centrifugation over a discontinuous sucrose density gradient as previously described (Yao et al, 2009). For fractionation of TGN microdomains, TGN-enriched fractions were isolated and subjected to carbonate extraction and discontinuous sucrose density centrifugation as previously described (Waugh et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For fractionation of PM microdomains, MBECs from three confluent 160-mm-diameter dishes were harvested and PM isolated and subjected to detergent-free sodium carbonate extraction and centrifugation over a discontinuous sucrose density gradient as previously described (Yao et al, 2009). For fractionation of TGN microdomains, TGN-enriched fractions were isolated and subjected to carbonate extraction and discontinuous sucrose density centrifugation as previously described (Waugh et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…We first took a biochemical approach to assess partitioning of caveolin-1 and syntaxin-6 to membrane domains isolated from cell lysates. To avoid artifacts related to lipid reassembly during detergent extraction (Lichtenberg et al, 2005), we used a detergent-free, carbonate-based extraction method for microdomain fractionation (Song et al, 1996;Yao et al, 2009). Golgi-or PM-enriched membranes from cell lysates were sonicated, extracted with carbonate to remove loosely associated proteins, and separated by centrifugation over a sucrose density gradient.…”
Section: Cln3 Modulates Membrane Microdomain Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Four-step sucrose density gradient fractionation was performed as described previously (Kwon et al, 2013;Yao et al, 2009) to separate the HLDM from the LLDM plasma membrane fraction. The purified plasma membrane pellet from HEK293T cells was resuspended with 2 ml of 500 mM sodium carbonate, pH 11.0, homogenized using ten strokes of a Dounce homogenizer, and mixed with 2 ml of 90% sucrose in MBS buffer.…”
Section: Separation Of Lipid Microdomains Of Plasma Membranementioning
confidence: 99%
“…Therefore, we aimed at deciphering the underlying mechanism of these rapid nongenomic effects. Here, we showed that a fraction of the cellular RARa pool is present in membrane lipid rafts, which are microdomains of cell membranes enriched not only in cholesterol and sphingolipids but also in signal-transducing molecules, such as flotillins, G proteins-coupled receptors, heterotrimeric G proteins, Rho and Rac GTPases, and their effectors (Pike, 2003;de Laurentiis et al, 2007;Sugawara et al, 2007;Yao et al, 2009). In lipid rafts, G proteins consist of three subunits a, b and g, and transmit signals to downstream effector molecules such as phospholipase C, proteinkinase C and p38MAPK (Mizuno and Itoh, 2009).…”
Section: Introductionmentioning
confidence: 99%